Analisis Kesiapan Aktor Pelaksana dalam Pelayanan Satu Pintu Dinas Pendidikan Kota Surabaya - Hermawanti, Dhea Ayu Putri (IAI Nasional Laa Roiba Bogor, 2025)
Bureaucratic reform is a strategic step aimed at achieving good governance by enhancing efficiency and effectiveness in public services. One of the innovations implemented by the Education Office of Surabaya City is the One-Stop Service system, which is designed to simplify access for the community by allowing them to visit just one location for services. This study aims to analyze the extent of the readiness of the service providers in delivering effective, efficient, and quality services, utilizing five indicators from Martin Jr.'s theory, namely: (1) Proficiency in using equipment; (2) Readiness; (3) Responsibility in service; (4) Discipline; (5) Employee attitude. The method used in this research is qualitative descriptive, with data collection conducted through interviews, observations, and literature studies. The findings indicate that the readiness of employees in the One-Stop Service at the Education Office of Surabaya City plays a crucial role in enhancing the quality of public service to the community.